PENERAPAN PENDEKATAN TEACHING AT THE RIGHT LEVEL (TaRL) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V SD INPRES 6/75 MAJANG KABUPATEN BONE - Sudirman; Rukayah; Nuraina Ramadhani (STKIP Subang, 2026)
This research aims to describe the implementation of the Teaching at The Right Level (TaRL) approach to improve the reading comprehension ability of fifth-grade students at SD Inpres 6/75 Majang, Bone Regency, and to determine whether the approach can improve that ability. This study is a Classroom Action Research using a qualitative approach, carried out in two cycles following the planning, acting, observing, and reflecting stages of the Kemmis and McTaggart model. The subjects were the fifth-grade teacher and all 18 fifth-grade students. Data were collected through observation sheets and reading comprehension tests, then analyzed through data reduction, data display, and conclusion drawing. The results showed that teacher activity increased from 58.33% (fair) in cycle I to 83.33% (good) in cycle II, while student activity increased from 58.33% (fair) to 75% (good). The reading comprehension test results showed that 10 of 18 students (55%) reached the success indicator in cycle I, increasing to 13 of 18 students (72%) in cycle II. It is concluded that the implementation of the Teaching at The Right Level (TaRL) approach can improve the reading comprehension ability of fifth-grade students at SD Inpres 6/75 Majang, Bone Regency.